Model Guided Teaching dalam Pembelajaran IPS untuk Meningkatkan Partisipasi Belajar Siswa - Daranis Daranis (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2017)
Background of this study is the low learning participation of 6th grade students’ in social subject learning. This study aimed to improve students’ participation in social subject learning through implementation of guided teaching model. This is a classroom action research which was conducted at SDN 18 Batang Anai. Data were collected through observation of teacher’s activity, observation of students’ participation, and test of students’ achievement. There are three observed indicators of participation: proposing idea, answering question, and asking question. For cycle I, percentage of students’ participation in proposing idea is 34.37% and 78.12% for cycle II. Percentage of students’ participation in answering question is 37.49% for cycle I and 81.25% for cycle II. Furthermore, percentage of students’ participation in asking question is 26.16% for cycle I and 75.00% for cycle II. There is also improvement of students’ learning achievement. It is 46.87% in cycle I and 87.50% in cycle II. Hence, implementation of guided teaching model in social subject learning can improve students’ participation.